1991
DOI: 10.1111/j.1365-3083.1991.tb03751.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD40 and CD43 during Activation of Human B Lymphocytes

Abstract: CD40 and CD43 are two cell-surface glycoproteins that appear to be functionally involved in the growth stimulation of human B cells. Whereas CD40 is structurally similar to the NGF receptor and is present on all resting B cells, CD43 displays no homology to other known proteins and is expressed only on a subpopulation of these cells. To further understand the extra- and intracellular signals regulating these molecules and in which stage of activation they may play a role, we used various activation strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…The use of TG mice to study the disregulation of a putative adhesion/cell signaling molecule within a lineage where it normally functions provides a powerful in vivo approach that in turn may reveal functions not predicted by in vitro studies. Here we have shown that mCD43, previously used as a cell surface developmental marker (27)(28)(29)(30)(47)(48)(49), is involved in programmed cell death in the B-cell lineage and results in increased B-cell numbers. Disregulation provides a complementary approach to gene "knockouts," achieved by homologous recombination, for understanding the function of developmentally regulated genes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The use of TG mice to study the disregulation of a putative adhesion/cell signaling molecule within a lineage where it normally functions provides a powerful in vivo approach that in turn may reveal functions not predicted by in vitro studies. Here we have shown that mCD43, previously used as a cell surface developmental marker (27)(28)(29)(30)(47)(48)(49), is involved in programmed cell death in the B-cell lineage and results in increased B-cell numbers. Disregulation provides a complementary approach to gene "knockouts," achieved by homologous recombination, for understanding the function of developmentally regulated genes.…”
Section: Discussionmentioning
confidence: 97%
“…This strategy was based on the fact that the mCD43 promoter is already active in parts of the B-cell lineage (27)(28)(29)(30) and that the immunoglobulin heavy chain enhancer can support augmented expression even from heterologous promoters (42). Our finding that the mCD43-Ig heavy chain enhancer fusion gene is expressed at high levels in mature peripheral B cells indicates that the immunoglobulin enhancer sequence exerts a dominant influence on mCD43 transgene expression, with a developmental program consistent with that of the immunoglobulin heavy chain itself (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether CD2:Stat6VT B cells are activated or simply have increased expression of Stat6-inducible genes, we analyzed the expression of other cell surface markers that indicate activation or maturation of B lymphocytes and are not regulated by IL-4. FACS analysis of freshly isolated B220 ϩ cells from wildtype and CD2:Stat6VT mice showed that CD40 expression, which is up-regulated on activated or mature B lymphocytes (43)(44)(45), was increased on transgenic B cells compared with wild type (Fig. 5A).…”
Section: Stat6vt Does Not Induce An Activated Phenotype In B Lymphocytesmentioning
confidence: 99%